A New Approach for Characterizing Pile Heat Exchangers Using Thermal Response Tests - Charles Maragna; Fleur Loveridge (Energies, 2021)
Pile heat exchangers offer a cost effective route to implementation of ground-source heat pump systems for many large commercial buildings compared with traditional boreholes. Such projects typically use thermal response tests to determine the key input parameters for system design, namely soil thermal conductivity and heat exchanger thermal resistance. However, this brings challenges for pile heat exchanger based systems, where in situ thermal response tests are known to be less reliable due to the large thermal capacity of the pile. This paper presents a new “black box” resistance capacitive model for applications to pile thermal response tests. The approach is tested against case study data and shown to perform well. Additional test duration savings are shown to be possible if a novel combination of borehole and pile thermal response tests is applied together to determine design parameters.